Family and neighbourhood socioeconomic inequalities in childhood trajectories of BMI and overweight: Longitudinal Study of Australian Children. - Mensah, Fiona K; Jansen, P; Wake, M; Nicholson, J; Mensah, F; Wake, Melissa; Nicholson, Jan M (My University, 2013)
Background: Socioeconomic inequalities in longitudinal patterning of childhood overweight could cause marked differentials in total burden by adulthood. This study aims to determine timing and strength of the association between socioeconomic status (SES) and children’s body mass index (BMI) in the pre- and primary school years, and to examine socioeconomic differences in overweight trajectories across childhood. Methods: Participants were 4949 children from the Longitudinal Study of Australian Children. BMI was measured at four biennial waves starting at age 4–5 years in 2004. Developmental trajectories of childhood overweight were identified with latent class analyses. Composite variables of family and neighbourhood SES were used. Results: Socioeconomic differences in mean BMI z-scores already present at age 4–5 more than doubled by age 10–11 years, reflecting decreasing mean BMI among advantaged rather than increasing means among disadvantaged children. Latent class analysis identified children with ‘stable normal weight’ (68%), and with ‘persistent’ (15%), ‘late-onset’ (14%), and ‘resolving’ overweight (3%). Risks of persistent and late-onset childhood overweight were highest among low SES families (e.g. most disadvantaged quintile: ORpersistent = 2.51, 95%CI: 1.83–3.43), and only partly explained by birth weight and parental overweight. Relationships with neighbourhood SES were weaker and attenuated fully on adjustment for family SES. No socioeconomic gradient was observed for resolving overweight. Conclusions: Childhood has become the critical period when socioeconomic inequalities in overweight emerge and strengthen. Although targeting disadvantaged children with early overweight must be a top priority, the presence of childhood overweight even among less-disadvantaged families suggests only whole-society approaches will eliminate overweight-associated morbidity.
Plos One
Keywords: Health -- Obesity; Children -- Early childhood; Health -- Body size, BMI, Body image; Disadvantage -- Socio-economic index for areas; Health and wellbeing; Children; Disadvantage; Health; Body size, BMI, Body image; Socio-economic index for areas; Obesity; Early childhood; Health and wellbeing